Quantification and kinetic analysis of Grb2-EGFR interaction on micro-patterned surfaces for the characterization of EGFR-modulating substances. - Peter Lanzerstorfer (Public Library of Science (PLoS), 2014)
The identification of the epidermal growth factor receptor (EGFR) as an oncogene has led to the development of several anticancer therapeutics directed against this receptor tyrosine kinase. However, drug resistance and low efficacy remain a severe challenge, and have led to a demand for novel systems for an efficient identification and characterization of new substances. Here we report on a technique which combines micro-patterned surfaces and total internal reflection fluorescence (TIRF) microscopy (μ-patterning assay) for the quantitative analysis of EGFR activity. It does not simply measure the phosphorylation of the receptor, but instead quantifies the interaction of the key signal transmitting protein Grb2 (growth factor receptor-bound protein 2) with the EGFR in a live cell context. It was possible to demonstrate an EGF dependent recruitment of Grb2 to the EGFR, which was significantly inhibited in the presence of clinically tested EGFR inhibitors, including small tyrosine kinase inhibitors and monoclonal antibodies targeting the EGF binding site. Importantly, in addition to its potential use as a screening tool, our experimental setup offers the possibility to provide insight into the molecular mechanisms of bait-prey interaction. Recruitment of the EGFR together with Grb2 to clathrin coated pits (CCPs) was found to be a key feature in our assay. Application of bleaching experiments enabled calculation of the Grb2 exchange rate, which significantly changed upon stimulation or the presence of EGFR activity inhibiting drugs.